Recalibration of benchmarks is necessary: even the most basic meal was not affordable for Malawi’s poor between 2017 and 2021 - Bwanaisa, Mercy; Hendriks, Sheryl L. (Frontiers in Sustainable Food Systems, 2023)
Dietary quality has significant implications for health, nutrition and life quality. Yet, most people in developing countries, such as Malawi, consume inadequate diets due to the high cost of healthy and nutritious food. The international community has called for a radical transformation of food systems to ensure access to healthier food options at affordable prices. While the costs and affordability of healthy and nutritious diets have recently been established, little attention has been paid to the economic accessibility of basic nourishment. The most available price data (2017 to 2021) from the National Statistics Office of Malawi (NSO) were used to calculate the cost of the World Food Program’s ‘basic plate’. Food items were substituted to determine if local substitutes could improve the nutritional value of the plate. The plate cost was compared to the international poverty line and average food expenditure in Malawi. Slight variations in the purchase parity cost and affordability of basic meals were found between 2017 and 2021. However, the basic meal and alternative plates were not affordable to those living at or below the international poverty line over this period. A revision of the poverty line is necessary to ensure that basic nutritional needs can be met. Both revisions of the poverty line and cash-based food assistance should consider that meals using animal-sourced proteins were more expensive than plant-based protein sources, but animal-sourced proteins provide more nutrition than plant-based protein meals.